Pengaruh Intellectual Capital, Keputusan Investasi dan Kebijakan Dividen Terhadap Nilai Perusahaan - Rosanti, Rosanti; Azzahra, Khoirunnisa (JURNAL AKUNTANSI BARELANG, 2024)
This study aims to provide empirical evidence of the effect of Intellectual Capital, Investation Decision, and Dividend Policy on The Value of The Company. This study uses a quantitative approach and the data used is secondary data. The population in this study were Properties & Real Estate companies listed on the Indonesian Stock Exchange fot the period 2018 – 2022. The method in determining the sample use purposive sampling. Obtained a sampel of 7 company with a period 5 years. The data analysis technique used is multiple linear regression analysis. The F test result show that simultaneously Intellectual Capital, Investation Decision, and Dividend Police have a significant effect on the Value of The Company. The t test results show the Intellectual capital and Investation Decision partially no significant effect on The Value of The Company, while Dividend Policy partially has a significant effect on Company Value.